Blockchain-Based Peer-To-Peer Energy Trading Marketplace in Solar Energy - Atiq Firdaus, Fazari; Nazreen, Junaidi; A’in Sarah, Aidell; Shirley, Rufus (2024)
This research explores the application of blockchain technology in the energy trading sector, focusing on peer-to-peer solar energy trading. By leveraging Ethereum and Solidity, the study develops smart contracts to create a secure, transparent, and efficient energy trading platform. The system was tested on the Sepolia Testnet, showing high transaction throughput and low latency, with a comprehensive security audit confirming its robustness. Despite limitations such as the reliance on a test network and the need for additional functionalities, the findings demonstrate blockchain's potential to enhance transparency and security in energy trading. Future work includes real-world implementation and further optimization. This study contributes to the development of sustainable and reliable decentralized energy solutions.